2022
DOI: 10.1161/circinterventions.121.011768
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Based Differences in Periprocedural Complications Following Lower Extremity Peripheral Vascular Intervention

Abstract: Background: Women with coronary artery disease are shown to have worse outcomes after percutaneous coronary intervention compared with men; however, less is known about sex-based outcomes following lower extremity peripheral vascular intervention (PVI) for symptomatic peripheral artery disease. The study aims to assess whether female sex is independently associated with periprocedural complications in patients undergoing PVI. Methods: Analysis includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…93 A study that aimed to assess whether female sex is independently associated with periprocedural complications in patients undergoing lower extremity peripheral vascular intervention by utilizing data from the Vascular Quality Initiative registry found that women were at higher risk of developing access site complications (odds ratio, 1.45 [95% CI, 1.35-1.57]; P<0.001) and had a higher risk of target lesion dissection (odds ratio, 1.36 [95% CI, 1.26-1.46]; P<0.001), above-knee amputation (odds ratio, 1.37 [95% CI, 1.18-1.58]; P<0.001), and inhospital mortality (odds ratio, 1.21 [95% CI, 1.07-1.38]; P=0.003). 94 Compared with men in the Vascular Quality Initiative over the study period, women were more likely to be Black (19.6% versus 14.6%, P<0.0010), Hispanic or Latino (6.7% versus 5.9%, P<0.001), and have obesity. Compared with men, women were less likely to be on ACE (angiotensin-converting enzyme) inhibitor/ARB (angiotensin receptor blockers), antiplatelet, oral anticoagulant, cilostazol, or statin therapy at admission.…”
Section: Endovascular and Surgical Revascularizationmentioning
confidence: 91%
See 2 more Smart Citations
“…93 A study that aimed to assess whether female sex is independently associated with periprocedural complications in patients undergoing lower extremity peripheral vascular intervention by utilizing data from the Vascular Quality Initiative registry found that women were at higher risk of developing access site complications (odds ratio, 1.45 [95% CI, 1.35-1.57]; P<0.001) and had a higher risk of target lesion dissection (odds ratio, 1.36 [95% CI, 1.26-1.46]; P<0.001), above-knee amputation (odds ratio, 1.37 [95% CI, 1.18-1.58]; P<0.001), and inhospital mortality (odds ratio, 1.21 [95% CI, 1.07-1.38]; P=0.003). 94 Compared with men in the Vascular Quality Initiative over the study period, women were more likely to be Black (19.6% versus 14.6%, P<0.0010), Hispanic or Latino (6.7% versus 5.9%, P<0.001), and have obesity. Compared with men, women were less likely to be on ACE (angiotensin-converting enzyme) inhibitor/ARB (angiotensin receptor blockers), antiplatelet, oral anticoagulant, cilostazol, or statin therapy at admission.…”
Section: Endovascular and Surgical Revascularizationmentioning
confidence: 91%
“…Compared with men, women were less likely to be on ACE (angiotensin-converting enzyme) inhibitor/ARB (angiotensin receptor blockers), antiplatelet, oral anticoagulant, cilostazol, or statin therapy at admission. 94 In a post hoc analysis, investigators aimed to evaluate sex-specific differences in MACE and limb events in the EUCLID trial. 66 They found that PAD severity and medical treatment were comparable between sexes, but prior lower extremity revascularization was reported less frequently in women (54.8% versus 57.3%, P=0.006).…”
Section: Endovascular and Surgical Revascularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, women with PAD, compared to men, have poorer quality of life because they are older, with multiple vessel involvement and more advanced disease [15]. In addition, studies demonstrated that women with symptomatic PAD were less likely to receive goal-directed medical therapy and showed a lower rate of open surgical revascularizations compared with men [16], while data about post-revascularization outcomes showed mixed results between the two sexes, with a higher risk of developing periprocedural complications after percutaneous revascularizations in female patients [17].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, women with PAD, compared to men, have poorer quality of life because they are older, with multiple vessel involvement and a more advanced disease [15]. In addition, studies demonstrated that women with symptomatic PAD were less likely to receive goal-directed medical therapy and showed a lower rate of open surgical revascularizations compared with men [16], while data about postrevascularization outcomes showed mixed results between the two sexes, with a higher risk of developing periprocedural complications after percutaneous revascularizations in female patients [17].…”
mentioning
confidence: 99%